Prognostic value of lymphocyte count for in-hospital mortality in patients with severe AECOPD - Yanlu Hu; Huanyu Long; Yang Cao; Yanfei Guo (BMC Pulmonary Medicine, 2022)
Abstract Background Patients with severe acute exacerbations of chronic obstructive pulmonary disease often have a poor prognosis. Biomarkers can help clinicians personalize the assessment of different patients and mitigate mortality. The present study sought to determine if the lymphocyte count could act as a risk factor for mortality in individuals with severe AECOPD. Methods A retrospective study was carried out with 458 cases who had severe AECOPD. For analysis, patients were divided into two groups on the basis of lymphocyte count: < 0.8 × 109/L and ≥ 0.8 × 109/L. Results Patients who fulfilled the criteria for inclusion were enrolled, namely 458 with a mean age of 78.2 ± 8.2 years. Of these patients, 175 had a low lymphocyte count. Compared to patients with normal lymphocyte counts, those with low counts were older (79.2 ± 7.4 vs. 77.5 ± 8.6 years, p = 0.036), had lower activities of daily living scores on admission (35.9 ± 27.6 vs. 47.5 ± 17.1, p < 0.001), and had a greater need for home oxygen therapy (84.6 vs. 72.1%, p = 0.002). Patients with low lymphocytes had higher mortality rates during hospitalization (17.1 vs. 7.1%, p = 0.001), longer hospital stay (median [IQR] 16 days [12–26] vs. 14 days [10–20], p = 0.002) and longer time on mechanical ventilation (median [IQR] 11.6 days [5.8–18.7] vs. 10.9 days [3.8–11.6], p < 0.001). The logistic regression analysis showed lymphocyte count < 0.8 × 109/L was an independent risk factor associated with in-hospital mortality (OR 2.74, 95%CI 1.33–5.66, p = 0.006). Conclusion Lymphocyte count could act as a predictor of mortality in patients with severe AECOPD.